Investigation of Dose Effect of ICRP110 Male and Female Head Phantoms During BNCT and PBFT by Monte Carlo Simulations - Korkut, H.; Korkut, T.; Singh, V. P. (National Research and Innovation Agency, 2025)
Boron Neutron Capture Therapy (BNCT) and Proton Boron Fusion Therapy (PBFT) are of great interest in the field of radiation oncology. These treatment methods may offer different advantages and disadvantages depending on the type of tissue involved, as well as the location and size of the cancerous area. In this study, radiation dose effect of BNCT and PBFT on the brain, one of the most sensitive organs of the human body, was examined comparatively, based on the ICRP110 male and female head phantom models by using GEANT4 Monte Carlo simulations. Additionally, some necessary LET (Linear Energy Transfer) calculations are also presented in the article. Dose, LET and Energy deposition values of GEANT4 calculations were presented for BNCT and PBFT therapies in details for male and female phanthom comparatively.